KEBIJAKAN KRIMINAL DALAM PENANGGULANGAN PERKAWINAN DI BAWAH UMUR - Mohd Din; Mujibussalim Mujibussalim; Eli Dani Isma (Dusturiyah: Jurnal Hukum Islam, Perundang-undangan dan Pranata Sosial, 2017)
Reproductive health married at a young age at risk of causing twice as likely to die in childbirth as compared to those aged 20-25 years, while under-15-year-olds may die five times. Young women who are pregnant, based on research will experience several things, such as will experience bleeding, miscarriage, and difficulty in the process of childbirth. Therefore, early marriage has many negative impacts that are very important to be known by both teenagers and parents. Underage marriage phenomenon is not new in Indonesia as in the case of Syech praise and Lutfiana ulfa that caused controversy in the year 2009 ago, there are hundreds of cases underage marriages that do not stick to the surface and expose the media. In rural areas, there are many cases of underage marriages, such as in the Takengon area, Aceh Tengah District, Aceh Province, there are many cases of underage marriage, how is criminal policy in prevention of marriage of minors? A pakah effort undertaken in countermeasures of marriage of minors in Takengon Regency Central Aceh? Although countermeasures have been undertaken but underage marriages are still rife due to the absence of specific and firm legal arrangements concerning marriage of minors. Minors under Law No. 1 of 1974 on Marriage are children aged 19 years for men and 16 years for women. Although it has been affirmed that the minimum age limit is allowed to marry by law, on the other hand it is given an exception for marriage. Keywords: Criminal, Marriage, Underage